COMPARING THE CYTOTOXIC POTENTIAL OF WITHANIA SOMNIFERA WATER AND METHANOL EXTRACTS - Pretorius, Etheresia; Oberholzer, Hester Magdalena; Becker, Petrus Johannes (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The plant Withania somnifera (Linn.) (Solanacea) is a well-known herbal medicine used in many parts of the world. It has anti-inflammatory, antioxidant, and antitumor as well as neural protective properties. It seems as if the two most active withanolide components, namely withaferin A and withanolide D, found in methanol (MeOH) extracts, are responsible for the anti-inflammatory and antioxidant properties of the plant. The current research evaluated and compared the cytotoxic potential of water and methanol extracts of W. somnifera using a combined crystal violet MTT and Neutral Red assay. MRC-5 cells, a human embryonic lung-derived diploid fibroblast cell line, were the cells of choice. We found that the three lowest concentrations (0.007, 0.042, 0.250 µg/ml) of the plant material extracted in double distilled H2O and MeOH do not differ significantly in any of the assays. We therefore suggest that low concentrations of MeOH extracts (up to 0.250 µg/ml plant material) do not cause cell damage to the MRC-5 cells, however, higher levels should be avoided as cell viability and cell numbers are negatively influenced.